BOOK REVIEW OF Gavrielides, T. & Lyons, B. (2019). Safeguarding and Empowering Crime Victims Training Manual: Restorative Justice and the Victims' Directive (Restorative Justice Series Book 8), London; Restorative Justice for All (RJ4All) Publications. (2019) - Walker, Lorenn
No abstract available